IMPLEMENTASI STRATEGI DIREKTORAT JENDERAL MINYAK GAS DAN GAS BUMI DALAM MEMFASILITASI PEMANFAATAN ABAHAN BAKAR NABATI (BIOFUEL) - , Rubiyatni ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Directorate General of Oil and Gas as an institution that has a vision that is the fulfillment of demand of industrial feedstock and fuel oil and natural gas, gas and or liquid of coal, methane gas from coal as well as achieving optimization of the State revenue from the oil and gas and increasing utilization of other materials, which is mandated to facilitate the utilization of biofuels . To facilitate the utilization of Biofuels, Directorate General of Oil and Gas requires a strategy that is then implemented to find out how the implementation of the strategy of the Directorate General of Oil and Gas in facilitating the use of Biofuels in order to fit the target of minimum obligations based on EMR regulation No . 32 of 2008 which required a tool. This thesis proposes the concept of Balanced Scorecard to find out to what extent the strategy chosen has been implemented, by first making a strategy map which is then poured into a table Balanced Scorecard The results showed that by using the Balanced Scorecard, It can be seen the effectiveness of the strategy taken by the Directorate General of Oil and Gas in facilitating the utilization of Biofuels.